Culture dimensions and application of IFRSs in banking industry: what is the impact on loan loss provisions? - Lopes, A.I. (EAA 39th Annual Congress (European Accounting Association) - Presented Papers, 2016)
Loan loss provisions (LLP) are used as a proxy for credit risk for a long period of time. Using European and Asian banks, this paper investigates how differences in culture across different countries can be related with LLP based on the Hofstede’s theory. This paper also researches the effect of the use of IFRSs by the banking industry on the amount of LLP recognized in financial statements. Findings suggest that some culture dimensions plays a role when analyzing risk factors, but not in all situations. When scores based on characteristics and behavior attributable to national culture are conflicting [namely, low (high) scores of individualism (uncertainty avoidance) equivalent to low (high) scores of uncertainty avoidance (individualism)], the influence of culture on loan loss provisions is rejected. International Financial Reporting Standards (IFRSs) were also suggested as having an important role, positively increasing the power of national culture to influence the levels of LLP in countries where the scores to culture dimensions are according to the theory, and mitigating that influence when the scores are not consistent.